Inducible expression of truncated NAC62 provides tolerance against Alternaria brassicicola and imparts developmental changes in Indian mustard. (November 2022) - Mondal, Banani; Mukherjee, Amrita; Mazumder, Mrinmoy; De, Aishee; Ghosh, Swagata; Basu, Debabrata
Abstract: Indian mustard ( Brassica juncea) faces significant yield loss due to the 'Black Spot Disease, ' caused by a fungus Alternaria brassicicola. In plants, NAC transcription factors (NAC TFs) are known for their roles in development and stress tolerance. One such NAC TF, NAC 62, was induced during A. brassicicola challenge in Sinapis alba, a non-host resistant plant against this fungus . Sequence analyses of BjuNAC62 from B. juncea showed that it belonged to the membrane-bound class of transcription factors. Gene expression study revealed differential protein processing of NAC62 between B. juncea and S. alba on pathogen challenge. Furthermore, NAC62 processing to 25 kDa protein was found to be unique to the resistant plant during pathogenesis. Conditional expression of BjuNAC62ΔC, which lacks its transmembrane domain, in B. juncea showed improved tolerance to A. brassicicola . BjuNAC62ΔC processing to 25 kDa product was also observed in tolerant transgenic plants. Additionally, transgenic plants showed induced expression of genes associated with defense-related phytohormone signaling pathways on pathogen challenge. Again, altered phenotypes suggest a possible developmental effect of BjuNAC62∆C in transgenic plants. The overall results suggest that the processing of BjuNAC62 might be playing a crucial role in resistance response against Black Spot disease by modulating defense-associated genes. Highlights: Arabidopsis orthlogue of ANAC062 is present in Brassica juncea and Sinapis alba. This NAC TF, NAC62, possesses a C-terminal transmembrane domain (TMD). NAC62 is preferentially induced during Black Spot disease in S. alba . Processing of NAC62 to 25 kDa is unique to S. alba and associated with resistance Conditional expression of NAC62 ∆ C in B. juncea provides tolerance to this disease.